Sulfur-Doped and Bio-Resin-Derived Hard Carbon@rGO Composites as Sustainable Anodes for Lithium-Ion Batteries - Huang, Qinyuan; Hu, Jinbo; Wen, Shujing; Zhang, Xiang; Liu, Gonggang; Chang, Shanshan; Liu, Yuan (Frontiers in Chemistry, 2020)
Hard carbon derived from fossil products is widely used as anode material for lithium-ion batteries. However, there are still several main shortcomings such as high cost, and poor rate performance, which restrict its wide application. Then tremendous efforts have been devoted to developing biomaterials in the battery applications. Recently, especially agricultural and industrial by-products have attracted much attention due to the electric double-layer capacitors. Herein, we report the sulfur-doped hard carbon (SHC) materials from the tannin-furanic resins (TF-Resin) of the derived agricultural by-products, followed by enveloping rGO on its surface through the hexadecyl trimethyl ammonium bromide. SHC provides sites for the storage of lithium, while the rGO layers can offer a highly conductive matrix to achieve good contact between particles and promote the diffusion and transport of ions and electrons. As a result, the SHC@rGO shows excellent lithium storage performance with initial discharge capacity around 746 mAh g−1 at a current density of 50 mA g−1, and shows superb stability keeping capacity retention of 91.9% after 200 cycles. Moreover, even at a high current density of 2,000 mAg−1, SHC@rGO still delivers a specific capacity of 188 mAg−1. These desired promising properties are active to the implement in the possible practical application.